2021
DOI: 10.1136/bmjhci-2020-100187
|View full text |Cite
|
Sign up to set email alerts
|

Performance of national COVID-19 ‘symptom checkers’: a comparative case simulation study

Abstract: ObjectivesIdentifying those individuals requiring medical care is a basic tenet of the pandemic response. Here, we examine the COVID-19 community triage pathways employed by four nations, specifically comparing the safety and efficacy of national online ‘symptom checkers’ used within the triage pathway.MethodsA simulation study was conducted on current, nationwide, patient-led symptom checkers from four countries (Singapore, Japan, USA and UK). 52 cases were simulated to approximate typical COVID-19 presentati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…UK-wide, patients were advised to stay at home, book a SARS-CoV-2 test, and if concerned consult either an automated online symptom checker or non-clinical telephone triage system [ 12 , 13 ]. Notably, thresholds for onward referral using these new and unproven triage systems were high [15] . Equally concerning, the subsequent automated safety-net advice given to the patient included ‘how to manage breathlessness at home’ [13] – a practice that would have been inconceivable in 2019.…”
Section: The Rationed Responsementioning
confidence: 99%
See 2 more Smart Citations
“…UK-wide, patients were advised to stay at home, book a SARS-CoV-2 test, and if concerned consult either an automated online symptom checker or non-clinical telephone triage system [ 12 , 13 ]. Notably, thresholds for onward referral using these new and unproven triage systems were high [15] . Equally concerning, the subsequent automated safety-net advice given to the patient included ‘how to manage breathlessness at home’ [13] – a practice that would have been inconceivable in 2019.…”
Section: The Rationed Responsementioning
confidence: 99%
“…Unless the thresholds for onward assessment are set low, many opportunities to prevent disease progression will be missed, and with it the opportunity to reduce mortality, prevent post-pneumonia complications, and prevent prolonged and protracted hospital admissions. In the UK, the thresholds for recommending any clinical contact are set high, and not just for the areas suffering a surge of infections, but for the entire nation - restricting access to care even where healthcare demands are relatively low [15] .…”
Section: Pandemic Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptom checkers, which are self-directed risk assessments tools, has been shown to improve live quality and survival in oncology patients ( 2 ). Its use for COVID-19 is currently increasing and has been used to identify symptomatic patients or potential severe cases with the main objective to triage those individuals who would benefit from clinical assessment and/or management into further care ( 3 ). A recent French study showed that a national self-triage web application contributed to the alleviation of calls to the emergency calls centers and may be used for predicting increasing burden of hospital ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Symptom checkers are algorithm-based programs that provide potential virtual diagnoses and triage advice [17][18][19]. Symptom checkers promise a cost-effective way of enabling rapidly scalable epidemiological data collection and analysis, with varying diagnostic accuracy [20,21].…”
Section: Introductionmentioning
confidence: 99%